DEVELOPMENT OF TRAITS AND BEHAVIORS OF STARTUP ENTREPRENEURS - ปรัสพันธ์ จินตนา; Wattananarong, Krismant (Journal of Buddhist Anthropology, 2021)
The objectives of this article were to investigate traits and behavior and develop learning management as well as to investigate outcomes of learning management for development of traits and behavior of startup entrepreneurs. By being a research on the mixed methods. The purposive sampling method was used to select 891 undergraduate students as the samples for the study of traits and behavior. In investigating outcomes of learning management, the purposive sampling was also used to choose 55 students enrolling in e-commerce management courses in the second semester of the academic year 2020, Faculty of Management Science, Chandrakasem Rajabhat University; the experimental and control groups consisted of 33 and 22 students respectively. The data were tested normality and analyzed by mean, standard deviation, t-test and ANCOVAs. The results showed that traits and behavior of startup entrepreneurs comprised of 4 main aspects with 26 traits, namely intrinsic motivation (6 traits), management capabilities (11 traits), acceptance of change (6 traits), and creativity (3 traits). The development of learning management consisted of 5 steps, e.g. perception, response, value-creation, value system management, and character development. Eight teaching approaches were applied to cultivate knowledge, attitudes and behavior of startup entrepreneurs in students. In investigating effectiveness of the learning management process using KW#2, it was found that the process was effective in accordance with the established criteria (72.73/82.08). In terms of learning management outcomes, the experimental group achieved a higher score in the simulated situation test than the control group at a statistical significant level of 0.05. Results of ANCOVAs based on character test scores also showed that the simulated situation test score of the experimental group was different from that of the control group at a statistical significant level of 0.05.